İTAAT KÜLTÜRÜNÜN OLUŞMASINDA HADİSLERİN ROLÜ - İlyas Canikli (İslami İlimler Dergisi)
Throughout the history, the relationship between the rulers and the ruled ones has been developed in a specific hierarchical structure. The subjects concerning the quality of that relationship depend on that society. This is the same in Islamic political culture. The people who recognized Islam through the arrival of Divine Inspiration to Prophet Mohammed, implemented the doctrines of the Holy Koran and the practices (sunnas) of prophet Mohammed in their political lives. However, after the death of Prophet Mohammed, the matter of obedience hasn’t been evolved in accordance with the core values of the Holy Koran and the practices of Prophet Mohammed. Absolute obedience to the rulers isn’t discussed in the Holy Koran and it never existed in the Prophet Mohammed’s Prophet hood of 23 years. Contrary to that main conception, it is a common fact that there are some hadithes in the hadith litarature which bring the rulers’ rights in the foreground and force the ruled ones to abide them unconditionally. Accordingly, it is thought that it would be useful to re-read those hadithes in terms of their presence and accuracy. With the assistance of this article, it is aimed to make a contribution to the insight of the human being of the present day about the matter of obedience.